ANALISIS RISIKO SISTEM MANAJEMEN RANTAI PASOK MAMMA ROTI BERDASARKAN ISO 31000 - Pankrasius Aryo Wicaksono; Putra Arianto; Mirza Rabbani Kobandaha; Luthfi Jatmiko Nugroho; Ayasha Zahwa; Erly Krisnanik (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2026)
The Food & Beverages (F&B) industry in Indonesia faces complex challenges in managing supply chain operational risks, particularly for rapidly growing franchise companies like Mamma Roti established since 2021. This research aims to identify and analyze operational risks using the ISO 31000:2018 framework as a structured risk management standard. Descriptive qualitative method was applied through direct observation and semi-structured interviews, with analysis following stages of context establishment, identification, likelihood-impact matrix analysis, acceptance criteria evaluation, and risk treatment procedures. Research results identified twelve operational risks (R1-R12) with most at moderate levels, while two risks (R5 and R11) obtained critical scores of 9 related to continuous improvement mechanisms. Recommendations include implementing measurable action trackers, Service Level Agreements (SLA), concise Standard Operating Procedures (SOP), and Business Continuity Plan (BCP) and Disaster Recovery Plan (DRP) with Recovery Time Objective (RTO) of 2-24 hours. Mitigation strategies are expected to reduce risks within 1-3 months and enhance Mamma Roti's operational resilience.